Social Learning of Child Labor in Malang City: Albert Bandura's Theory Perspective - Rima Nabilah; Sopingi Sopingi; Retno Sulistiyaningsih; Umi Dayati; Endang Sri Redjeki (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2026)
Child labor has emerged as a prevalent social phenomenon, particularly in the city of Malang. This practice infringes upon children's rights, necessitating their adaptation to their environment through cognitive processes. Consequently, a learning process known as social learning is initiated. This study aims to analyze the social learning processes of child laborers and the factors influencing these processes within the context of Malang. Employing a qualitative case study approach, grounded in Albert Bandura's social cognitive theory, data was collected through in-depth interviews with three child labor informants. The findings reveal a multi-faceted social learning process encompassing four stages: attention, retention, reproduction, and motivation. A variety of factors were identified as influencing the social learning experiences of child laborers.